Posterior Capsular Opacification and Glistening in Hydrophobic Monofocal Biaspheric Intraocular Lens Two Years After Implantation: A Case Control Study - Ana Hervás-Ontiveros; Enrique España-Gregori; Carlos Fresno-Cañada; Rodrigo Butrón-Ruíz; Alejandro Cerviño (Journal of Ophthalmology)
Conclusion: Prevalence of PCO was considerably lower for Asqelio IOL than for the Control IOL and reports available in the literature for other hydrophobic IOLs. Prevalence of glistening was minimal in both study and control IOLs.